2004
DOI: 10.1007/978-3-540-30217-9_18
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Racing Techniques for Improved Empirical Evaluation of Evolutionary Algorithms

Abstract: Abstract. In empirical studies of Evolutionary Algorithms, it is usually desirable to evaluate and compare algorithms using as many different parameter settings and test problems as possible, in order to have a clear and detailed picture of their performance. Unfortunately, the total number of experiments required may be very large, which often makes such research work computationally prohibitive. In this paper, the application of a statistical method called racing is proposed as a general-purpose tool to redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 9 publications
0
36
0
Order By: Relevance
“…Some procedures for tackling the tuning problem have been proposed by Birattari [12]. Among them, the F-Race method is the best performing one and has been used in a number of works on metaheuristics [55,56,57,58,59].…”
Section: Literature Overviewmentioning
confidence: 99%
“…Some procedures for tackling the tuning problem have been proposed by Birattari [12]. Among them, the F-Race method is the best performing one and has been used in a number of works on metaheuristics [55,56,57,58,59].…”
Section: Literature Overviewmentioning
confidence: 99%
“…These approaches consider only the Pareto front set evaluation to improve MOEAs, whereas our approach evaluates operators contribution in improving fitness and thus injects mutation operators that are eligible to make MOEAs converge faster. In [37], the authors have shown that racing algorithms can be used to reduce the computational resources inherent from using evolutionary algorithms in large scale experimental studies, their approach automates solutions selection and discards solutions that do not introduce results improvement. Whereas racing techniques eliminate worst solutions candidates to speed up the search, in our approach we keep considering worst ranked candidates to maintain operators diversity.…”
Section: Related Workmentioning
confidence: 99%
“…Parameter tuning thus takes place before the run, e.g., exploiting the lessons learned from previous runs. Standard approaches from experimental studies such as ANOVA or Design Of Experiments have been used for parameter tuning, e.g., modeling the impact of parameter values on the overall performance and accordingly determining the optimal values [4,45,3,36]. These methods, however, are very computationally expensive, as each observation corresponds to the average of a few evolutionary runs; furthermore, static settings are usually considered (the parameter value is fixed along the run), whereas the optimal setting likely depends on the local landscape explored by the genetic population.…”
Section: Parameter Setting In Evolutionary Algorithmsmentioning
confidence: 99%